DEVELOPMENT OF AUTOMATIC TEMPERATURE CONTROL SYSTEM IN WAREHOUSES OF MULTITEMPERATURE TYPE CLASS "C" - Сарабєєв, Павло Ігорович; Носко, Павло Леонідович; Башта, Олександр Васильович; Мельник, Володимир Борисович; Герасимова, Ольга В’ячеславівна (Problems of Friction and Wear, 2024)
In the development of centralized temperature control systems with analog bus, the issues of error reduction are investigated. The main errors of such a system are the quantization error and the error due to noise. Based on the analysis of devices, design schemes and methods for noise immunity, it was recommended: to reduce the error due to noise by introducing a phase-locked loop (PLL) system that regulates the phase of the proposed controlled generator so that it corresponds to the reference signal phase or differed from the function known over time. A comparative analysis of existing methods has shown that the most effective method of measuring frequency is the "method of dependent measurements", which takes the best of the previous two and is accurate, fast and noise-proof. For warehouses of multi-temperature type of class "C" the automatic control system of temperature of the centralized type on the analog bus which has high technical characteristics is offered, namely: speed - time of standing on a point less than 0.1 seconds; the system multiplicative error does not exceed 0.15%, and the additive reduced error is equal to 0.05%; noise immunity is reduced from 30% error to almost zero. The system consists of N identical modules of signal input of sensors of non-electric quantities - resistive R1 (or capacitive C1), which are included in the frequency-forming units of PWM modulators. 8 sensors are connected to each of the modules. One of the sensors in the next module is selected using the DaisyChained serial control bus or the serial SPI peripheral interface. The use of such systems is cost-effective and allows for small premises to significantly expand the market for warehousing products.